THE RELATIONSHIP BETWEEN LEADERSHIP SKILLSAND PROPORTIONS OF WOMEN IN TOP LEADERSHIP POSITIONS - Ogutu, Dr.Dorcas Anyango; Ogollah, Dr. Kennedy (European Journal of Business and Strategic Management, 2016)
Purpose:In 2000 the United Nations member states ratified and committed themselves to achieving the eight millennium development goals. The most salient of the goals is number three that sought to promote gender equality and empower women. Despite the new constitution and other affirmative measures that have been undertaken by the Government of Kenya, there is still low representation of women in leadership in Kenya. The study sought to the relationship between leadership skills and proportion of women in top leadership positions in Kenya. The justification was driven by the realization that despite the affirmative action measures and the promulgation of the new Kenyan constitution which prohibits either gender from constituting more than two-thirds of any elected body, there has not been much progress in increasing the number of women in leadership positions. Methodology:This thesis used mixed method methodology (qualitative and quantitative). The study design was cross a sectional study and the data was collected using structure questionnaires, with closed ended questions for quantitative data and open ended questions for qualitative data. 221 senior managers in state corporations were sampled using stratified sampling technique. The questionnaires were self administered. Results:The findings indicate a positive relationship between Leadership Skills and Proportion of Women in Top Leadership Positions.The findings of this study suggest that leadership skills hinder the progression of women to high leadership positions in state corporations in Kenya. Unique contribution to theory, practice and policy: The thesis makes an important contribution in understanding the factors influencing proportion of women in top leadership positions in state corporations in Kenya. This study contributes to the theorythrough discussion of local and international literature on culture, leadership skills, family determinants and political considerations, affirmative action and gender mainstreaming issues were discussed. Literature on gender was thus used to make policy recommendationon organizational leadership.Female leaders have proved to be very effective in the current competitive world of business.